(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In this article discussed that, importance of interdisciplinary integration, some of the requirements and conditions for the introduction of integrated education in the primary grades, and described in detail the general features of the integrated course.